2009
DOI: 10.2165/00002512-200926060-00005
|View full text |Cite
|
Sign up to set email alerts
|

Use of Antipsychotics among Elderly Nursing Home Residents with Dementia in the US

Abstract: Nearly one-third of elderly nursing home residents with dementia received antipsychotic medications, mainly atypical agents. Predisposing, enabling and need factors influenced the use of atypical agents in dementia patients. These findings suggest a need to optimize use of atypical antipsychotics in elderly dementia patients in nursing homes in the light of recent efficacy and safety data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
73
2
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 33 publications
7
73
2
3
Order By: Relevance
“…In contrary to other studies, females were found to be the most utilizer of antipsychotics in our study [5,6,[11][12][13][14]. This may be due to the higher incidence and prevalence of mental health morbidities as well as the total visits in psychiatric clinics among females than males as reported in the annual report of Ministry of Health in Oman (MOH) [10].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrary to other studies, females were found to be the most utilizer of antipsychotics in our study [5,6,[11][12][13][14]. This may be due to the higher incidence and prevalence of mental health morbidities as well as the total visits in psychiatric clinics among females than males as reported in the annual report of Ministry of Health in Oman (MOH) [10].…”
Section: Discussioncontrasting
confidence: 99%
“…It also forms a database for future research and pattern comparison. The ratio for use of atypical: typical antipsychotics in our study (2.3:1) is somehow similar to what is reported in Western world and higher than other developing countries [5,9,[11][12][13][14]. One reason for this might be attributed to the economic status of the countries.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Previous studies in the U.S., the Netherlands, and Canada reported that the prescription rates of antipsychotics in LTCFs differ according to the characteristics and culture at the facility level, independent of individual characteristics, even in the same country. 15,16,19,20 However, there are no residing physicians in Korean LTCFs. Physician visits occur every two weeks, but prescriptions within the institution are prohibited by law, and necessary prescriptions can only be issued in external hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…53 This model has been previously used in studies involving medication use. [54][55][56] According to this model, health care use is a function of predisposing, enabling, and need factors. Predisposing factors are the characteristics of an individual that exist before the illness and include demographic characteristics, social structure characteristics, and health beliefs.…”
Section: Conceptual Frameworkmentioning
confidence: 99%